P-142 Hold the Phone: Presence of Concurrent Mood Disorders May Be Associated with Excess Patient-Physician Communication in Patients with IBD. (February 2017) - Davis, Emily; Testa, Stephen; Alsaadi, Dana; Borum, Marie
Abstract : Background: An individual's mental health can have a significant effect upon medical conditions. In inflammatory bowel disease (IBD), the presence of an inadequately controlled comorbid psychiatric illness may impact a patient's ability to understand and appropriately follow treatment regimens and self-manage symptoms. As a result, these patients may contact their physician more frequently following appointments seeking advice in managing their illness. This study evaluated the telephonic and electronic communication with physicians by IBD patients who had a comorbid psychiatric diagnosis compared to IBD patients without a comorbid psychiatric diagnosis. Methods: A retrospective chart review was performed of all patients with a diagnosis of IBD who had an outpatient clinic visit during a 6-month period at an urban university gastroenterology clinic. Demographic information including age, gender, and ethnicity were recorded as well as total number of telephonic and electronic communications with physician following their appointment. Communications were categorized as either <2 or 32 communications. The presence of a documented comorbid psychiatric diagnosis including anxiety, depression, PTSD, or bipolar disorder was also recorded. Patients taking an antidepressant without a documented psychiatric diagnosis were excluded from the study. Statistical analysis was conducted using a 2-tailed Fisher's Exact Test with a significance set at P < 0.05. Results: A total of 271 patient charts were reviewed, of which, 266 were included in the analysis. The patient population was comprised of 116 (43.6%) males and 150 (56.4%) females, with a mean age of 43.1 years. Ulcerative colitis accounted for 110 (41.4%) diagnoses and Crohn's disease for 156 (58.6%). The study included 141 (53%) Caucasians, 81 (30.5%) African Americans, 6 (2.3%) Latinos, 9 (3.4%) Asians, and 29 (10.9%) of other or undocumented ethnicity. A total of 43 (16.2%) patients had a comorbid psychiatric diagnosis. Data showed that 14 of 43 patients (32.6%) with a psychiatric diagnosis and 41 of 223 patients (18.4%) without a psychiatric diagnosis communicated with the provider following their appointment 2 or more times during the 6-month period. IBD patients with a comorbid psychiatric disorder contacted their physician regarding management significantly more ( P = 0.0414) than patients without a comorbid psychiatric disorder. There was no significant difference in the number of communications in IBD patients with coexisting psychiatric disorders based on gender ( P = 1) or ethnicity ( P = 0.49). Conclusions: Patients with an underlying psychiatric diagnosis may not be able to effectively manage treatment of IBD if their psychiatric symptoms are not adequately stabilized. One consequence of this may be frequent communication with their physician. Consideration should be given for assessing patients with IBD who access the healthcare system more frequently than expected for an underlying psychiatric diagnosis, and those with known psychiatric diagnosis should be assessed for adequate management of their psychiatric symptoms. The status of a patient's mental health is important in optimizing IBD management. Identifying and managing comorbid psychiatric illnesses in IBD patients should be encouraged.